The Action of the Holy Spirit in Freeing from Unconscious Mimetic Behaviour - Krzaczek, Krzysztof (Teologia w Polsce, 2020)
Violence originates from unconscious mimetic behaviour that can be observed in different cultures since the beginning of human history. Scapegoats were the way to deal with unbearable internal tensions, not only in individuals but also in whole societies. This process was thoroughly investigated by René Girard and Raymond Schwager. In my work, I would like to briefly describe this process and then show the role of the Holy Spirit in the liberation from these mechanisms. In the third part, based on the teaching of the fruits of the Holy Spirit, I will show how the active presence of the Paraclete creates completely new attitudes and virtues in a human person in response to these unconscious mimetic behaviours.